2019
DOI: 10.3390/jfb10030031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of In Vitro Immune Response Assessment for Biomaterials

Abstract: Grafts are required to restore tissue integrity and function. However, current gold standard autografting techniques yield limited harvest, with high rates of complication. In the search for viable substitutes, the number of biomaterials being developed and studied has increased rapidly. To date, low clinical uptake has accompanied inherently high failure rates, with immune rejection a specific and common end result. The objective of this review article was to evaluate published immune assays evaluating biomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 65 publications
2
52
0
Order By: Relevance
“…The in vitro assessment of macrophage immune responses to biomaterials is crucial to offer insights into the reasonable biomaterial designs, and several studies have demonstrated the good match between in vitro and in vivo results. [ 241 ] However, the conclusions from in vitro studies cannot be directly translated to the in vivo, since how the macrophages respond to biomaterials in vitro and in vivo are not always consistent. Furthermore, after entering into the body, the properties of biomaterials can change and differ in what macrophages encounter in vivo.…”
Section: Material‐modulated Macrophage Fatementioning
confidence: 99%
“…The in vitro assessment of macrophage immune responses to biomaterials is crucial to offer insights into the reasonable biomaterial designs, and several studies have demonstrated the good match between in vitro and in vivo results. [ 241 ] However, the conclusions from in vitro studies cannot be directly translated to the in vivo, since how the macrophages respond to biomaterials in vitro and in vivo are not always consistent. Furthermore, after entering into the body, the properties of biomaterials can change and differ in what macrophages encounter in vivo.…”
Section: Material‐modulated Macrophage Fatementioning
confidence: 99%
“…15 It has been found that material surface characteristics such as porosity, smoothness and shape play a role in cell attachment and the ability for tissue ingrowth, and thus is a factor to consider prior to using the CAM for bone tissue engineering evaluation of materials. 13 Prior in vitro testing of materials, concepts and functions of biomaterials is mandatory and the importance of examining the potential immune response is reviewed by Lock et al 16 The CAM is a highly vascular construct, with vessels forming through a process of sprouting and intussusceptive mechanisms, as the CAM expands rapidly between EDs 9 and 11 and, more slowly, between EDs 12 and 14. 17 The CAM is fully formed between EDs 8 and 10, with the ability to withstand grafts and scaffolds and in addition, is responsive to stimuli at this time 18 (Figure 2).…”
Section: The Cammentioning
confidence: 99%
“… 15 It has been found that material surface characteristics such as porosity, smoothness and shape play a role in cell attachment and the ability for tissue ingrowth, and thus is a factor to consider prior to using the CAM for bone tissue engineering evaluation of materials. 13 Prior in vitro testing of materials, concepts and functions of biomaterials is mandatory and the importance of examining the potential immune response is reviewed by Lock et al 16 …”
Section: The Cammentioning
confidence: 99%
“…The high failure rates with frequent rejection of implants in clinic might be decreased using in vitro immune assays to predict the outcome prior to in vivo applications (Oliveira and Mano, 2014;Kohli et al, 2018;Lock et al, 2019). There are in vitro biomaterial immunogenicity assays applied based on immature human cell lines and peripheral blood mononuclear cells (PBMCs) to assess material-induced cell viability, maturation, activation, chemotaxis, and protein secretion (Smith et al, 2009;Anderson and McNally, 2011;Franz et al, 2011;Yahyouche et al, 2011;Kou et al, 2012;Spiller et al, 2014;Sussman et al, 2014;Lock et al, 2019;Przekora, 2019;Segan et al, 2020). An increased number of HLA molecules on the cell surface is an established inflammatory marker (Park and Babensee, 2012;Musson et al, 2015), suggesting the next step, to find out which peptides are presented to T cells in higher numbers after contact with the biomaterial.…”
Section: Introductionmentioning
confidence: 99%